Comparison of al-'Asha and Jarir in Panegyrical and Satirical Themes - Ebau, Fauwaz (2011)
The research addresses the comparison between Al-’Asha and Jarir which aims to study the jointly purposes of their poetry in praise and satire. It also investigates the statement by their peers that Al-’Asha in pre-Islamic age is Jarir in Islamic age. It highlights the importance of pre-Islamic and Umayyad poetry especially in two significant arts including praise and satire. The research also highlights the differences and similarities between the two poets in praise and satire, showing their importance as famous poets who have poetry status in society, and comparing between them in the purposes of praise and satire. The researcher also applied an inductive approach by tracking their poems regarding praise and satire in different reference books and original sources of history and literature books as well as modern references. After the examination of the literature review, the researcher adopted the descriptive and analytical methods to compare between the two poets. The finding of this study includes that there are significant similarities between Al-’Asha and Jarir in terms of the development of their poetry, the formulation of the poems and their purposes of poetry. They were distinguished in the rhythm of music that helped their poems to spread prominently in their eras and became popular. The study supported the critical statement which claimed that the peer of Al-’Asha in pre-Islamic age is Jarir in Islamic age, which is the main purpose of the research.